Development of A Holistic Spiritual Education Model in Higher College: A Multidisciplinary Perspective - Khozin Khozin; Eka Firmansyah (Universitas Muhammadiyah Palu, 2024)
This research aims to develop a holistic spiritual education model in higher education with a multidisciplinary approach. Spiritual education is becoming increasingly important in the context of higher education, considering the demand for the formation of individuals who not only develop intellectually, but also emotionally, spiritually and morally. This research uses a qualitative approach, with a case study type of research. This research analyses the spiritual education practices at Muhammadiyah University Palu. The data collection techniques used were interviews, documentation and observation. This research involved interviews with education, spirituality and multidisciplinary figures to obtain diverse points of view. The results of this research explain a holistic spiritual education model that combines principles from various scientific disciplines, such as psychology, philosophy, anthropology, and theology. This model will also provide practical guidance for other universities to integrate spiritual aspects in the curriculum and learning activities on campus. It is hoped that the development of this holistic spiritual education model can make a significant contribution in building the character and well-being of students, as well as preparing them to face complex challenges in their personal and professional lives in the future.